Demography of Eastern Population Tundra Swans Cygnus columbianus - Bart, Jonathan; Limpert, Roland; Earnst, Susan; Sladen, William; Hines, James; Rothe, Thomas (Wildfowl, 2013)
We present rates of productivity and survivorship during the first year of life for Eastern Population Tundra Swans based on several extensive data sets. Our main objective is to illustrate how such data can be used to construct a life table for populations that are inaccessible except by aerial survey on the breeding grounds or that migrate long distances and disperse over wide areas, and thus that are difficult to study via intensive long-term investigations. Our data were obtained from the northwestern third of the breeding range of Eastern Population Tundra Swans and throughout their wintering range during 1967-1989. An average of 77% of the sampled birds apparently held territories in the spring, 34 % of them nested successfully, and the number of young per successful nest was 2.46. Survivorship during the first migration averaged 52% and during the first winter averaged 76%. We identify the additional information needed to construct a life table from these estimates and discuss problems encountered in using extensive survey data for these purposes.